Museum Collections as a Reflection of Cultural Landscape: the Interpretation of Collective Memory - Habjanič, Oskar; Verena Perko (European Journal of Multidisciplinary Studies, 2018)
The article deals with the relationship between the local community, museum collections, collective memory and the cultural landscape. The ICOM Code of Museum Ethics defines a museum collection as a cultural and natural heritage of the communities from which they have been derived. The collections, especially in regional museums, are inextricably linked to the community. The cultural landscape can be read also as a bridge between the society and natural environment. The cultural landscape is vitally connected with a national, regional, local, ethnic, religious or political identity. Furthermore, the cultural landscape is a reflection of the community’s activities. Therefore, private collections are the foundation of the collective memory and empower museums for important social tasks. They offer an opportunity for multilayered interpretation of the past and give a possibility for museums to work on the inclusion of vulnerable groups. The collections could be a mediator and unique tool for recovering of the “broken” memory. In this way certain tragic past events, ignored or only bigotedly mentioned by history, can be re-evaluated.